Temporary Loop Occlusion using Vessel Loops on Bilateral Common iliac Arteries to Reduce Blood Loss in Total Abdominal Hysterectomy on Adherent Placenta Patient at Sanglah General Hospital, Bali-Indonesia - I Nyoman Semadi (Journal of Global Pharma Technology, 2020)
Background: In pregnancy, there may be an invasion of the placenta into uterine wall, causing post-partum haemorrhage. This Hemorrhage may cause maternal death. Therefore a total abdominal hysterectomy (TAH) needs to be done to stop the bleeding. Temporary loop occlusion (TLO) is an additional procedure to reduce blood loss when doing TAH. This study aims to determine the intraoperative outputs of TLO when doing TAH on adherent placenta patient. Material & Method: This research is a retrospective study conducted at Sanglah Hospital from January 1st to 31st December 2019. There were two groups consist of four patients each, namely TLO intervention and non-intervention. Each group was analyzed based on the estimated blood loss, the number of packed red cell (PRC) transfusion, operating time, length of intensive care unit (ICU) and ward stay. Result: Intraoperative blood loss revealed a statistically significant difference in results (p=0.037), with mean 2125 ± 853.9 ml in TLO intervention and 3750 ± 866 ml in non-intervention. Comparison between both groups on other variables such as PRC transfusion were 694.75 ± 394.18 ml and 1298.5 ± 716.19 (p=0.384), operating time were 220,05 ± 39,5 minutes and 264,5 ± 69,84 minutes (p=0.468), length of ICU stay were 2.75 ± 0.95 days and 3.25 ± 0.96 days (p=0.488), length of ward stay were 2.25 ± 0.5 days and 2.75 ± 1.5 days (p=0.85). Conclusion: TLO is an additional procedure that can be performed on TAH because it provides good output. Keywords: Temporary loop occlusion, Hysterectomy, Adherent placenta, Haemorrhage, outcome.